Analisis Kedisplinan Kerja Terhadap Kinerja Karyawan Di Koperasi Serba Usaha Banteng Muda Indonesia Mandiri - Ary Martias Tarigan; Enda Noviyanti Simorangkir (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
The study aims to determine leadership-based leadership on how employees work in taking action whether leadership can be able to provide the best service to do something beyond what is targeted to customers. In addition, the company's leadership must be able to improve work discipline in order to carry out the work properly and directed so that the leadership provides successful performance that has a positive effect on each employee so that they have their own commitment in improving employee performance discipline so that all can run well in improving the way of working. comfortably.